Structures and neuroprotective activities of triterpenoids from Cynomorium coccineum subsp. songaricum (Rupr.) J. Leonard. (June 2022) - Zhang, Bo; Yang, Sheng-Li; Li, Xin; Zhang, Qian-Ru; Tian, Meng-Yin; Wang, Xiao-Liang; Wang, Su-Juan
Abstract: Cynomorium coccineum subsp. songaricum (Rupr.) J. Leonard has been widely used as a Chinese herbal remedy or a functional food for treating symptoms of aging or neurodegenerative diseases. A further investigation on the finding of active constituents led to the isolation and identification of four previously undescribed triterpenoids, together with 20 known compounds. Their structures were elucidated by extensive spectroscopic analysis (IR, NMR, HRMS, and CD). Sixteen compounds showed significant neuroprotective effects against glutamate-induced or oxygen-glucose deprivation-induced SK-N-SH cell death. Our findings revealed the active constituents of C. coccineum subsp. songaricum and indicated that both oleanane-type and ursane-type triterpenes could be valuable platforms for neurodegenerative agents based on primary structure-activity relationship analysis. Graphical abstract: Four previously undescribed triterpenoids, together with 20 known compounds were isolated from Cynomorium coccineum subsp. songaricum (Rupr.) J. Leonard. Sixteen compounds showed significant neuroprotective activities. Image 1 Highlights: Four previously undescribed triterpenes along with 20 known compounds were isolated. Sixteen compounds showed significant neuroprotective activities. The neuroprotective acitivities of most triterpenes are firstly reported. Oleanane/ursane-type triterpenes are valuable platforms for neuroprotective agents.